La « femme·eux·ze » musique québécoise : La recherche sur les genres, les sexualités et autres pratiques non dominantes en musique au Québec (1874-2022) - Blais-Tremblay, Vanessa (Centre de recherche interuniversitaire sur la littérature et la culture au Québec [CRILCQ], 2023)
C’est là un ouvrage de référence qui présente la recherche sur la musique, les genres et les sexualités, et plus largement la vie musicale non dominante au Québec depuis le dernier quart du XIXe siècle jusqu’à aujourd’hui. Issu des travaux réalisés en 202-2022 par le pôle universitaire DIG! Différences et inégalités de genre dans la musique au Québec (D!G), un réseau interdisciplinaire et intersectoriel qui réunit les chercheur·ses, publics, artistes et autres professionnel·les de la musique qui s’intéressent à cette thématique, l’ouvrage comprend une revue de la littérature et une bibliographie de plus de 800 ressources scientifiques.

Interpreting Brazilianness: Reception and Representation in the Brazilian Music Scenes of Toronto and Montreal - Mercier, Catherine G. (Université de Toronto, 2014)
In Toronto and Montreal, Brazilian popular music performances constitute a context for intercultural encounter. Performances offer Brazilians the opportunity to present their culture of origin while emphasising their identification with it. The issue of representation is quite complex, however, due to the involvement of a majority of non-Brazilian musicians, audience members, artistic directors, producers, promoters, and journalists. This dissertation focuses on music reception and cultural representation and how these may influence each other after music has been decontextualised and recontextualised. I look closely at local non-Brazilian audiences possessing different degrees of familiarity with Brazilian music, and I demonstrate how cultural stereotypes influence their conceptions and expectations of Brazilian music, culture, and people. I argue that a desire for cultural difference and the exotic, encouraged by discourses of cultural diversity, influences the reception of performances. I suggest that, through the privileged gaze of non-Brazilian attendees, performances may be adjusted to correspond to audience fantasies of Brazil. Some non-Brazilians would like to become knowledgeable of, and even intimate with Brazilian culture, which would satisfy their desire to be cosmopolitan. However, pleasure frequently matters more to them than a nuanced understanding of Brazilian culture; this explains, I contend, why some Torontonians and Montrealers have become comfortable with essentialist and stereotypical representations. I examine how some non-Brazilian musicians, promoters, and band agents reinforce mythologies of Brazil to meet audience demands and sometimes to satisfy their own fantasies. I analyse the reproduction of similarly problematic discourses on Brazil in the presentations of Brazilian artists as both a form of autoexoticism and a particular type of tactical or strategic essentialism. Rather than to represent and understand Brazilian culture, I argue that, through local music performances, Brazilians and non-Brazilians in Toronto and Montreal interpret Brazilianness.

Polyrhythmic Dance Currents: Race Multiculturalism and the Montreal Dance Community - Templeton, Melissa (Université de Californie à Riverside, 2012)

The Odyssey of Dahlia Obadia: Morocco, Israel, Canada - Sawa, Suzanne Myers (Canadian Folk Music Journal, 1991)
Dahlia Obadia interprète les danses de la tradition du moyen orient. Pendant sa carrières, elle a rémarque qu’il existe des grandes différences entre les interprétations de cette tradition vue de l’intérier et de l’extérieur. L’auteur décrit la vie de Dahlia et explore les problèmes qu’elle a affrontes pendant sa quête de sa propre identité culturelle.